2014
DOI: 10.1108/jpif-01-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment-based commercial real estate forecasting with Google search volume data

Abstract: Purpose – The purpose of this paper is to examine internet search query data provided by “Google Trends”, with respect to its ability to serve as a sentiment indicator and improve commercial real estate forecasting models for transactions and price indices. Design/methodology/approach – This paper examines internet search query data provided by “Google Trends”, with respect to its ability to serve as a sentiment indicator and improve com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…There is no existing measure of property buyers' incentives. We follow the literature (Dietzel et al, 2014;Kulkarni et al, 2009;Wu & Brynjolfsson, 2015) to measure buyers' incentives using Google Trends data. Google Trends does not report the raw level of queries for a given search term.…”
Section: Measuring Prospective Buyers' Incentives In Hong Kongmentioning
confidence: 99%
“…There is no existing measure of property buyers' incentives. We follow the literature (Dietzel et al, 2014;Kulkarni et al, 2009;Wu & Brynjolfsson, 2015) to measure buyers' incentives using Google Trends data. Google Trends does not report the raw level of queries for a given search term.…”
Section: Measuring Prospective Buyers' Incentives In Hong Kongmentioning
confidence: 99%
“…Redden (2016) argued that the development of activity nodes such as information technology (IT) Parks, special economic zones (SEZs), and industrial estates boost the city's economy and create a firm employment base in holy cities. Dietzel et al (2014); Glaeser et al (2014) found that there is a huge scope for the service industry in the diasporic cities where the demand for office space is usually of grade A and grade B office spaces. Bamossy (2011) found that the residential sector is a big hit in holy cities attracting both Indian and foreign crowd, who seek to buy their second/retirement homes in the holy city.…”
Section: Extrinsic Attributes and Gentrification Of Holy Citiesmentioning
confidence: 99%
“…The author observed that: (i) the asset prices will be positively affected by stable inflationary policy over the long term, (ii) unemployment figures would continue exhibit downward trend in most major markets in the globe which would lead to a boom in the real-estate sector, (iii) commodity prices that affect consumers and the real estate market would not reflect any significant rise in the near future. Dietzel et al (2014) examined the role of Internet search data in the commercial real estate sector. The authors constructed various forecast models and found that the inclusion of Google search data significantly improves the forecast results of commercial real estate prices for the US market.…”
Section: Related Workmentioning
confidence: 99%